Investigation of ultrasonic guided wave inspection on a wing spar structure - Nazeer, Nakash (Nanyang Technological University, 2021)
In recent years, ultrasonic guided waves have proven to be a reliable and fruitful method for examining large structures. The capability of inspecting areas that are unreachable or inaccessible is what gains our interest. This thesis investigates the guided wave propagation in an isotropic spar structure. The focus is on the 0th order shear horizontal wave mode (SH0) below the cut-of frequency of SH1 mode which is 1.6 MHz-mm. A fundamental study is carried out using a 2D system examining the propagation in the straight plate part and also in the circumferential bend region. A wave mode is chosen appropriately to carry out the wave propagation characteristics. The curvature effects are examined by comparing the group velocity, displacement, stress and strain distributions between a flat and curved plate for various curvature ratios. The frequency dependence of the distributions are also looked upon. These parameters are seen to be varying across the thickness of the bend and are also frequency sensitive. Reflections arising purely from the bends are also analysed. 2D guided wave scattering from transverse defects and delamination present along the bend region are also investigated. The study is carried out in a 2D and 3D domain. The effect of frequency on the scattering is also studied. This provides a graphical tool to understand how different defect placements and sizes interact with the waves. The distribution of energy across the thickness of the bend also helps in understanding which frequency range is more sensitive to defects present towards the inner, outer or mid region of the bend. Results of Finite Element (FE) modelling were validated by experiments.